The Improvementof English Speakingskills Throughcollaborativelearning Usingmovieasmedia Abstract (ActionResearchattheEnglishLiteratureStudyProgramofDarmaPersadaUniversity) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The purpose of this study is to determine in detail the process and results of the   Englishspeaking skills improvement through collaborative learning using movie as media. This researchisanactionresearchconductedintheEnglishliteraturestudyprogramofDarmaPersadaUniversity. Data obtained from the results of the English speaking skills test before and after theaction. The results showed that the collaborative learning process using movie as media madestudents' speaking skills increase, they became more active during the learning process. It was indicate dby the level of the irparticipationin learning interactions. There sults of the improvement in English speaking skills have increased quite significantly from the pre-actionstage to the third cycle in the research process. This action research carried out with collaborativelearning using movie as media significantly helps students to improve their skills in speakingEnglish. This learning has also proven to be able to make students work well and shape theirenthusiasm forlearning.